PENGARUH KUALITAS PELAYANAN CUSTOMER RELATION TERHADAP KEPUASAN PENGUNJUNG DI MAL SKA PEKANBARU - Sianipar, Ronita Uli Sari; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Customer Relations is a front liner in charge of serving every visitor who needs information around SKA Pekanbaru mall. Various forms of service are given customer relations is to make visitors feel comfortable and satisfied with what they receive. The following indicators of the quality of services to be tested, including physical evidence, reliability, ability to respond, assurance and empathy. It is assessed to see how much influence the visitor satisfaction, which the indicators themselves include suitability and expectations. The theory used in this research is S-O-R theory. The purpose of this study is to determine how much influence the quality of customer relationship service to the satisfaction of visitors in SKA Pekanbaru mall.This research uses explanative quantitative research method, with data collection technique is distributing questionnaires to 384 visitors in SKA Pekanbaru mall, with accidental sampling technique that is choosing anyone who happened to be found to be sampled. And the technique of data analysis in this research using simple linear regression analysis technique.The results of this study indicate that the value of regression coefficient in this study is Y = 3.856 + 0.250 X. The constant number (a) of 3.856 and the coefficient of variable X of 0.250. Meanwhile t count 34,090 bigger when compared with t table equal to 1,966, with significance level 0.000 less than α = 0,05. Based on the statistical calculation, the hypothesis for this research is Ha there is influence between service quality (X) to visitor satisfaction (Y). Then it means Ha accepted Ho rejected. And based on the table "Model Summary" shows that the value of R = 0.868 and the coefficient of determination (Rsquare) is 0.753 result of the correlation coefficient correlation 0.753 x 0.753. This number indicates that the contribution of variable quality of service (X) to visitor satisfaction (Y) is 75.3% with STRONG category. While the rest of 24.7% influenced by other variables not included in this study. This means that the quality of service has an effect on the satisfaction of visitors in SKA Pekanbaru mall, and the influence of the strong category of 75.3%.Keyword : Service quality, Customer relation, Visitor satisfaction